2022
DOI: 10.3390/jcm11206000
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to Violet Light Emitted from Eyeglass Frames in Myopic Children: A Randomized Pilot Clinical Trial

Abstract: Violet light (VL), 360–400 nm wavelength, is contained in the sunlight and is an effective element for myopia suppression. This study is to investigate the safety and efficacy of novel eyeglasses that emit VL from the frames. This is a double-masked, randomized, pilot clinical trial conducted in a clinic in Japan. Forty-three children with myopia were enrolled. Participants were randomly assigned to two groups, wearing VL-emitting eyeglass frames (VLf) that emitted VL of 310 μW/cm2 (VLf group, n = 22) or pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Simultaneously, the prevalence of UV light overprotection has led to no VL indoors. A recent randomized controlled trial (RCT) has shown that short-term exposure to violet light could be effective in inhibiting the progression of myopia and leading to a significant increase in the ChT [97]. We reported that exposure to VL in the 360-400 nm range can upregulate the gene early growth response protein (EGR-1) expression and slow myopia progression [98].…”
Section: Choroidal Changes With Light Exposurementioning
confidence: 98%
See 1 more Smart Citation
“…Simultaneously, the prevalence of UV light overprotection has led to no VL indoors. A recent randomized controlled trial (RCT) has shown that short-term exposure to violet light could be effective in inhibiting the progression of myopia and leading to a significant increase in the ChT [97]. We reported that exposure to VL in the 360-400 nm range can upregulate the gene early growth response protein (EGR-1) expression and slow myopia progression [98].…”
Section: Choroidal Changes With Light Exposurementioning
confidence: 98%
“…This figure shows the choroidal blood flow change and myopia correlation. (A) Normal choroidal perfusion and normal choroidal thickness; (B) studies proved a reduction in choroidal perfusion leads to a decrease in choroidal thickness and axial elongation; (C) anti-myopia treatment and increased perfusion lead to choroidal thickness maintenance and suppression of axial elongation.Created with graphics from ©BioRender (biorender.com)[9,10,19,32,50,56,57,67,69,97,98,100].…”
mentioning
confidence: 99%
“…34 Paradoxically, in experiments involving human subjects, short-term (1 h) exposure to monochromatic blue (460 nm) lighting also resulted in a reduction in axial length, while increases in axial length and choroidal thinning were observed after 1 h in green (521 nm) and red (623 nm) monochromatic lighting. 35 Furthermore, Tsubota and colleagues hypothesised that exposure to 'violet light' (<400 nm) would inhibit myopia in children, reporting preliminary data in support of this idea, 36 although only a fraction of light at such short wavelengths is expected to penetrate the human ocular media and so reach the retina. Interestingly, data from chickens indicate that they respond more 'like the humans', 35 becoming more myopic when reared in red light.…”
Section: Is There An Ideal Wavelength For Inhibiting Myopia?mentioning
confidence: 99%
“…There is a growing evidence which indicate that specific wavelengths of light may play a probable role in controlling myopia. 103 Apart from the low level repeated red-light therapy through desktop-based device, 104 there are a few wearable devices for myopia control that are developed to emit monochromatic light: violet light from eyeglass frames, 102 and blue light simulation of optic nerve head using virtual reality headset, 105 which are currently being investigated in the myopia clinical trials. There is a wide scope for the wearable light therapy devices as myopia control intervention, in addition to optical and pharmaceutical interventions.…”
Section: Future Perspectivesmentioning
confidence: 99%